Using health economic modelling to inform the design and development of an intervention: estimating the justifiable cost of weight loss maintenance in the UK - Sarah E. Bates; Chloe Thomas; Nazrul Islam; Amy L. Ahern; Penny Breeze; Simon Griffin; Alan Brennan (BMC, 2022)
Abstract Background There is a need to develop cost-effective weight loss maintenance interventions to prolong the positive impact of weight loss on health outcomes. Conducting pre-trial health economic modelling is recommended to inform the design and development of behavioural interventions. We aimed to use health economic modelling to estimate the maximum cost per-person (justifiable cost) of a cost-effective behavioural weight loss maintenance intervention, given an estimated intervention effect for individuals with: i) a Body Mass Index (BMI) of 28 kg/m2 or above without diabetes and ii) a diagnosis of type 2 diabetes prescribed a single non-insulin diabetes medication. Methods The School for Public Health Research Diabetes prevention model was used to estimate the lifetime Quality-adjusted life year (QALY) gains, healthcare costs, and maximum justifiable cost associated with a weight loss maintenance intervention. Based on a meta-analysis, the estimated effect of a weight loss maintenance intervention following a 9 kg weight loss, was a regain of 1.33 kg and 4.38 kg in years one and two respectively compared to greater regain of 2.84 kg and 5.6 kg in the control group. Sensitivity analysis was conducted around the rate of regain, duration of effect and initial weight loss. Results The justifiable cost for a weight loss maintenance intervention at an ICER of £20,000 per QALY was £104.64 for an individual with a BMI of 28 or over and £88.14 for an individual with type 2 diabetes. Within sensitivity analysis, this varied from £36.42 to £203.77 for the former, and between £29.98 and £173.05 for the latter. Conclusions Researchers developing a weight loss maintenance intervention should consider these maximum justifiable cost estimates and the potential impact of the duration of effect and initial weight loss when designing intervention content and deciding target populations. Future research should consider using the methods demonstrated in this study to use health economic modelling to inform the design and budgetary decisions in the development of a behavioural interventions.